The use of digital twins to remotely update feedback controllers for the motion control of nonlinear dynamic systems. (15th February 2023) - Vered, Yoav; Elliott, Stephen J.
Highlights: A digital twin is employed to ensure the stability of a mechanical system with an uncertain nonlinear sandwiched backlash. A time-varying backlash is modelled and used in the simulation to represent wear processes. A PID controller with a dead zone switching law is used to avoid limit cycles and restabilize the system. Asynchronous communication and buffers are utilized to ensure constant sampling time and reduce the controller complexity. Abstract: The use of a digital twin to update a feedback controller is considered, and this is illustrated using simulations of a position-controlled dynamical system with a time-varying nonlinear element. The feedback control system consists of a dc motor driving the displacement of a three degree of freedom structure through a lead screw that is subject to backlash, whose gap angle changes over time due to wear for example. The backlash is shown to destabilise the feedback loop when using a PID controller designed for the linear system. However, stability can then be re-established by including a dead zone within the controller. The design of the dead zone depends on the extent of the gap angle in the backlash and is a trade-off between stabilising the system and avoiding excessive steady-state errors and undesired transient behaviour. When the backlash gap angle changes significantly from the one used to design the dead zone, both performance and stability are affected. Therefore, a digital twin of the system is used to estimate the backlash gap angle as it changes with time and this estimate is used to re-design the dead zone, which is then communicated back to update the controller. The digital twin and controller-design process can be implemented offline and remotely from the physical twin and the real-time controller via an asynchronous link with variable time delays. As a result of combining the feedback loop and digital twin, good performance and stability are maintained at all times.